Tanggung Jawab Prinsipal Terhadap Konsumen Dalam Perjanjian Keagenan Dan Distributor - Sudjana Sudjana (Universitas Serang Raya, 2022)
This study aims to determine the Legal Existence of Agency and Distributor Agreements in the Civil Law Perspective and Principal Responsibilities to Consumers in Agency and Distributor Agreements. The research method used is a normative juridical approach, the research phase is a literature study, data collection technique is through document studies and normative qualitative data analysis. The results of the study show that the existence of an Agency and Distributor Agreement in the Civil Law Perspective is an anonymous agreement and is categorized as a power of attorney although not entirely because it is more of a fiduciary relationship, while the distributor agreement is basically a sale and purchase agreement as regulated in Article 1457 until Article 1540 of the Civil Code, so that the distributor is not the power of the principal but acts on his own behalf. The principal is responsible for consumers who feel aggrieved in the agency agreement based on the principle of absolute responsibility because the agent acts in the interests of the principal, so that the agent is not responsible for losses incurred on the consumer's side due to the use of goods and services produced by the principal unless the agent exceeds his authority or changes goods that are the object of the agreement based on the principle of presumption of responsibility are not always guilty. The principal in the distributor agreement is not directly responsible for consumers who have a legal relationship with the distributor, except for product defects through the principle of presumption of not always being responsible. The distributor acts on his own behalf, not on the principal's orders, so that the distributor is responsible if the consumer feels aggrieved based on the presumption of always being guilty.